Factors Supporting and Hindering the Learning of English as an Additional Language Experienced by a Female Indonesian Student - Purwati, Diana (Jurnal Sains Sosio Humaniora, 2020)
This study investigates factors supporting and hindering a female Indonesian learner in learning English as an Additional Language (EAL). Data were taken through a semi-structured interview. Findings suggested that personal factors (motivation and learning style), and environmental factors (immersion in targeted language, the teacher’s strategy and supporting English study club) have been classified as supporting factors of the participant in learning English. However, environmental factors, such as lack of supportive environment and learning anxiety, had contributed to hindering the participant in learning English. Suggested pedagogic implication, such as utilizing communicative method and promoting a sense of self-direction are offered at the end of this study.